The giant ciliate Zoothamnium niveum and its thiotrophic epibiont Candidatus Thiobios zoothamnicoli: a model system to study interspecies cooperation - Bright, Monika; Espada-Hinojosa, Salvador; Lagkouvardos, Ilias; Volland, Jean-Marie (Frontiers in Microbiology, 2014)
Symbioses between chemoautotrophic sulfur-oxidizing (thiotrophic) bacteria and protists or animals are among the most diverse and prevalent in the ocean. They are extremely difficult to maintain in aquaria and no thiotrophic symbiosis involving an animal host has ever been successfully cultivated. In contrast, we have cultivated the giant ciliate Zoothamnium niveum and its obligate ectosymbiont Cand. Thiobios zoothamnicoli in small flow-through aquaria. This review provides an overview of the host and the symbiont and their phylogenetic relationships. We summarize our knowledge on the ecology, geographic distribution and life cycle of the host, on the vertical transmission of the symbiont, and on the cultivation of this symbiosis. We then discuss the benefits and costs involved in this cooperation compared with other thiotrophic symbioses and outline our view on the evolution and persistence of this byproduct mutualism.